Problematika Penelitian Filologi: Tinjauan dari Perspektif Edisi Teks dan Kajian Teks - Istadiyantha Istadiyantha (Manuskripta, 2011)
Philological work is used to pure the text by having criticism toward the text, and the textual criticism objective is to produce a text which is most equivalent with the source. The text which has been cleared from the error and has been reorganized as the original is a text which can be responsible as a source for many researches in other disciplinary knowledge. Some people regard that editing text is not a research. This assumption is not true because the text editing in the scope of philology must be based on the study using textual criticism method. The manuscript transliteration which is not through critical edition has many weaknesses. Due to the high possibility that the text purity cannot be proved scientifically, meaning that the text validity will be doubtful. Hence, any text analysis must be initially by a critical edition or philological study. The philological analysis through critical edition can be developed to the other form of analysis by using literal and multidisciplinary methods. It can be done after it has been known the content of the edited text previously. Therefore, the philological expert has much opportunity to understand any other relevant disciplinary and the philological science, since to understand the other relevant science in order that the text is appropriate to the recent context and the text is suitable with the text situation when the text is written, it can be separated from the other disciplinary science.